Portfolio Optimization by Quadratic Programming - Rianingsih, Wahyu; Hasan, Moh.; Pradjaningsih, Agustina (Majalah Ilmiah Matematika dan Statistika, 2017)
Portfolio is amount of investment. It determines proportion of fund that should be allocated in each investment in order to increase a certain profit with a certain risk. This research has aim to achieve an optimal result of portfolio case. Examaning this case is use quadratic programming, and then finishing with Wolfe method.